A Distributed Algorithm for Area Partitioning in Grid-Shape and Vector-Shape Configurations with Multiple Aerial Robots - Acevedo, José Joaquín; Arrue, Begoña C.; Maza, Ivan; Ollero, Anibal (Journal of intelligent & robotic systems, 2016)
Partitioning strategies have proven to be the more efficient solutions to patrol cooperatively an area with multiple aerial robots from a frequency-based approach. They allow to obtain theoretically the optimal performance keeping periodical communications between the robots. Therefore, it allows to coordinate the robots from a distributed manner even under communications constraints. Assuming that the whole area is divided as a r × c grid, this paper proposes a new distributed algorithm where each robot divides the whole area allocation problem in two (one for its row and another for its column) and solves them in an independent manner based on the coordination variables. Moreover, this new algorithm is validated and compared from a convergence time point of view with respect to other previously presented methods.